Storage Profiling: Evaluating the Effect of Modified Atmosphere Packaging on Metabolomic Changes of Strawberries (Fragaria × ananassa) - Johannes Brockelt; Robin Dammann; Jennifer Griese; Agnes Weiss; Markus Fischer; Marina Creydt (Metabolites)
Background/Objectives: Strawberries (Fragaria × ananassa) are among the most commonly consumed fruits due to their taste and nutritional benefits. However, their high rate of spoilage poses a major problem during the period from harvest and transport to further processing or marketing. The aim of this study was, therefore, to investigate the effects of passive modified atmosphere packaging on the metabolome and shelf life of strawberries as a more sustainable alternative compared to standard market storage conditions. Methods: A total of 99 strawberry samples were analyzed for microbial viable counts, water content, and metabolomic changes using non-targeted low-resolution near-infrared spectroscopy, high-resolution mass spectrometry, and microbial culture-based methods. Results: Using near-infrared spectroscopy as a rapid screening method, the linear regression model indicated that strawberries stored under modified atmosphere packaging conditions had a longer shelf life. Furthermore, lipidomic analysis using mass spectrometry showed that the levels of spoilage biomarkers, such as oxidized phosphatidylcholines and lysophosphatidylcholines, were increased under common market storage conditions without a controlled atmosphere. In contrast, the levels of these metabolites were reduced when strawberries were stored in modified atmosphere packaging. Moreover, the strawberries stored under modified atmosphere packaging had a lower number of bacteria, yeasts, and molds as well as a lower water loss throughout the entire storage period. Conclusions: Overall, the study highlights the potential of passive modified atmosphere packaging films to extend the shelf life and thus maintain the edibility of strawberries over a longer period.